Communicating across Age Lines: A Perspective on the State of the Scholarship of Intergenerational Communication in Health Sciences Libraries. Issue 1 (2nd January 2019) - McElfresh, Jenessa; Stark, Rachel Keiko
ABSTRACT: The purpose of this study was to review the existing literature on intergenerational workplace communication to identify trends or research pertaining to medical or health sciences library employees. Although the authors found no published literature that explicitly addresses intergenerational communication in health sciences libraries, it is worthwhile to explore the literature in related fields to identify applicable points of comparison to the experiences of health sciences librarians. This includes intergenerational communication research in management and leadership studies and medical literature, and the exploration of other intergenerational issues in the library literature.